Determinants of Economic Growth in Indonesia, Malaysia, and Thailand through Technological Growth, Foreign Direct Investment Growth, and Labor Force Participation Levels - Irma Nur Aysah; Niniek Imaningsih (Yayasan Riset dan Pengembangan Intelektual, 2024)
This research aims to identify the impact of the growth of internet users, “growth of foreign direct investment, and labor force participation rates on economic growth in Indonesia, Malaysia, and Thailand. The research method used is quantitative research using multiple linear regression and data obtained from the World Bank website. The data was then processed through classical assumption tests and hypothesis testing using the Eviews 10 econometric application. The research results show that partially, the growth of internet users has a negative and significant influence on economic growth in Indonesia. However, the growth of internet users has no influence on economic growth in Malaysia and Thailand. Apart from that, the growth of foreign direct investment has no influence on economic growth in Indonesia, but has a positive influence in Malaysia and Thailand. Meanwhile, the labor force participation rate has no influence on economic growth in Indonesia, Malaysia and Thailand”. Simultaneously, the growth of internet users, the growth of foreign direct investment, and the level of labor force participation have an influence on economic growth in Indonesia, Malaysia, and Thailand in the 2002-2021 period.